In-vitro Anti-cancer and Antioxidant Activity of Biogenically Synthesized Co3O4@NiO Core-shell Nanostructures - Gezahegn Ayanie; Tegene Zeleke; H.C Murthy; Lemma Tifa; Addisalem Godana (Nanomedicine Journal, 2025)
The anticancer and antioxidant activities of Datura stramonium plant leaf extract mediated Co3O4 and NiO nanoparticles, as well as Co3O4@NiO core-shell nanostructures were investigated. The Co3O4@NiO CSNs were synthesized with core-shell concentration ratios of 2:1, 1:1, and 2:3. The Co3O4@NiO CSNs and their parent nanoparticles were characterized by using advanced techniques. The band gap energy of Co3O4 (11) and NiO (11) NPs were found to be 3.06 eV and 3.45 eV, whereas, the band gap energies of the Co3O4 core and NiO shell were 3.68 and 4.52 eV, respectively. Similarly, the average crystalline size of Co3O4 (11) and NiO (11) NPs, as well as Co3O4@NiO (11) CSNs were found to be 18, 12, and 13 nm, respectively. The spherical shape of Co3O4, NiO NPs, and the spherical rod of Co3O4@NiO CSNs were investigated from SEM images. The particle sizes of cubic Co3O4, NiO NPs, and Co3O4@NiO CSNs obtained from TEM images were 15.55, 8.184, and 16.99 nm, respectively. The polycrystalline nature of CN was revealed from SAED analysis The percentage inhibition of Co3O4@NiO CSNs against MCF-7 cancer cells at 100, 200, 400, and 800 μg/mL were found to be 52.41, 68.21, 74.11, and 81.38%, respectively. The IC50 of Co3O4@NiO CSNs and epirubicin were found to be 21.25 and 18.01 μg/mL, respectively. The findings show that green synthesized Co3O4@NiO CSNs possess potential anticancer activities nearly comparable with standard drugs with less toxicity against normal cells.